Trump and the Al Qaeda and ISIS Networks in Africa - Christopher Griffin (Revue LISA)
President Donald Trump’s Africa policy is often characterized as one of indifference towards the continent. The news of four American soldiers killed in combat with ISIS on the border of Mali and Niger, however, demonstrated the reality of the situation, which is that American troops are increasing their involvement in counterterrorism on the continent. This paper uses the Niger incident as its starting point to examine the Trump administration’s military policy in Africa against Al Qaeda and ISIS affiliated groups. Trump’s rhetoric and stated policy about Africa contrasts with the reality on the ground, where the US considers the war on terrorism there to be strategically important. The presence of the US Army and its actions in Somalia, Libya, Niger and in Nigeria demonstrate that Trump has carried over some of the active military policies of George W. Bush and Barack Obama. Trump, however, has changed the US strategy from an emphasis on foreign aid and peacekeeping to a focus on the use of significant military force and firepower to defeat Al Qaeda and ISIS terrorist groups. The wars in Africa fit into Trump’s worldwide war on terrorism aimed at destroying Al Qaeda and ISIS, and in which the administration is prepared to accept significant American casualties.